The effects of incorporating a hockey stick in Speed, Agility and Quickness (SAQ) training on the speed and agility of youth field hockey players / Arif Iskandar Azhar ... [et al.]. - Azhar, Arif Iskandar; Mohamed, Muhamad Noor; Md Radzi, Noor Azila Azreen; Saiful Annur, Muhamad Safiq; Mazaulan, Mardiana; Adnan, Mohd Aizzat; Abu Kassim, Nurul Ain; Shari, Maisarah; Raja Hussain, Raja Nurul Jannat (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the effects of incorporating a hockey stick into Speed, Agility, and Quickness (SAQ) training for youth field hockey players. By addressing the lack of sport-specific adaptations in conventional training [1], it aims to improve speed and agility, offering evidence-based insights for enhancing performance through a novel Hockey Stick-enhanced SAQ (H-SAQ) program. Sixteen male youth field hockey players (ages 13–17) from Bukit Aman, Kuala Lumpur were divided into stick use (SU) and no stick (NS). A six-week Hockey Stick-Enhanced SAQ program with two 45-minute sessions per week featured drills like sprints, lateral jumps, and shuttles. Speed and agility were assessed pre- and post-training using the PSS-YP, anthropometric measures, 20-meter sprint, 20-meter sprint with a ball, and Illinois Agility Test.